Shell shape polymorphism analysis of the Manila clam Ruditapes philippinarum across different geographical populations in China - Huo, Zhongming; Wang, Zixuan; Li, Dongdong; Liu, Kuo; Li, Xiaotong; Fang, Lei; Yan, Xiwu (Frontiers in Marine Science, 2024)
Morphology of bivalves, a kind of quantitative character, is closely connected with the ecological and physiological behaviors of bivalves, such as growth, survival, metabolism, and reproduction. This study utilized a multivariate statistical method to analyze the seven shell shape evaluation indices of Ruditaps philippinarum (R. philippinarum). The polymorphism of R. philippinarum shell shape across seven geographical populations from the southern and northern regions of China was revealed, and the decisive effect of shell shape in determining the trait of weight was discussed. Three types of R. philippinarum shell shape were observed: globular, flat, and lateral view round shapes. The Laizhou (LZ) population from the north of China displayed an approximately globular shell shape, with a ratio of shell width to shell length of 0.5496 and an Ellipse index ventral view ( EIV ) value of 0.9543. The Lianjiang (LJ) population from the south of China displayed a flat shell shape, with a ratio of shell width to shell length of 0.4044, an Ellipse index lateral view ( EIL ) value of 1.2518, and an EIV value of 0.7063. The Zhangzidao (ZZD)population from the north of China displayed a lateral view round shell shape, with a shell width ratio to shell length of 0.7476 and a Circle index lateral view ( CIL ) value of 0.7195. Principal component analysis (PCA), discriminant analysis, and cluster analysis on shell shape parameters showed that the LJ and LZ populations could be grouped separately. Principal component analysis (PCA), discriminant analysis and cluster analysis on shell shape parameters showed that the LJ population and the LZ population could be grouped separately. However, in terms of shell shape traits, the Rongcheng (RC) population and the ZZD population shared more similarities, implying that these two populations might be more closely related. The lowest degree of divergence was observed in the Beihai (BH) population and the Yingkou (YK) population, both of which could be grouped into the Zuidong (ZD) population. The weight of globular Manila clams were significantly higher than that of flat clams (P < 0.05). This study lays a foundation for germplasm resource conservation of R. philippinarum.